2017
DOI: 10.24818/jamis.2017.04005
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the relationship between CSR disclosure and financial performance: The case of Polish banks

Abstract: Abstract:The purpose of this study is twofold. First, this study investigates the trends of corporate social responsibility (CSR) reporting and financial performance (FP) in commercial banks in Poland. Second, this study examines the impact of the CSR disclosure of the banks on their financial performance (ROA, ROE, NIM). Sample consists of 18 banks. The data from annual reports for the period of 8 years (2008 -2015) were both hand collected and obtained from Notoria Servis Database. A content analysis is use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 33 publications
1
29
2
1
Order By: Relevance
“…No relationship between CSR and FP was also presented in Soana [22], based on a sample of Italian banks. Similar results were found in Matuszak and Różańska [51], based on a sample of Polish banks. In conflict with the social impact hypothesis, statistical analysis showed that CSR did not significantly predict accounting returns.…”
Section: Literature Review and Development Of Hypothesessupporting
confidence: 87%
See 4 more Smart Citations
“…No relationship between CSR and FP was also presented in Soana [22], based on a sample of Italian banks. Similar results were found in Matuszak and Różańska [51], based on a sample of Polish banks. In conflict with the social impact hypothesis, statistical analysis showed that CSR did not significantly predict accounting returns.…”
Section: Literature Review and Development Of Hypothesessupporting
confidence: 87%
“…An individual investor should pay attention not only to his private social demands, but to those of other stakeholders as well. Previous studies regarding the CSR-FP link in the banking industry have adopted aggregated measures of the CSR construct, including reputation ratings such as the AEI Index [22], and other externally visible measures, such as ratings data from the MSCI ESG STATS database (formerly the KLD [53] or EIRIS Index [32]), as well as disclosure [51]. In this study, we employed content analysis of CSR information disclosed by banks, based on the multidimensional scale developed by Matuszak and Różańska [51].…”
Section: Dependent Variablesmentioning
confidence: 99%
See 3 more Smart Citations